Liver and Spleen Stiffness as Predictors of Esophageal Varices in Patients with Liver Cirrhosis - Jaishi, Shila; Pathak, Rahul; Bhandari, Brindeswari Kafle; Jha, Anurag; Hamal, Rabin; Koirala, Dinesh; Gyawali, Susmita (Journal of Institute of Medicine Nepal, 2023)
Introduction The risk stratification for the presence of esophageal varices in cirrhosis patient is assessed by two gold standard invasive tests: hepatic venous pressure gradient measurement and esophagogastroduodenoscopy. We aimed to find the relationship between spleen and liver stiffness with the presence of esophageal varices in a non-invasive way by means of transient elastography. Methods This was a cross-sectional study. In the study duration of one year, 94 cirrhotic patients who met the inclusion and exclusion criteria were included. All patients were subjected to transient elastography for measuring liver and spleen stiffness and endoscopy. Results Of 94 patients, only 77 (81.9%) had esophageal varices. The mean liver stiffness in patients with and without varices was 19.46±4.9SD kPa and 12.92±1.52 SD kPa respectively. The difference was statistically significant, p<0.001. The mean spleen stiffness in patients with and without varices was 22.26±4.6 SD kPa and 14.08±1.20 SD kPa respectively. The difference was statistically significant, p<0.001. The optimal cut off value of liver and spleen to detect patients with any grade of esophageal varices was 14 And 16.15 kPa respectively in this study. Conclusion The stiffness of liver and spleen using transient elastography can be considered an equivalent method for screening cirrhotic patients for esophageal varices in clinical settings.